2011
DOI: 10.1097/aog.0b013e3182118e98
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Postcesarean Infectious Complication Rates Using Two Different Skin Preparations

Abstract: The SCRUB+PAINT protocol is associated with a decrease in the rate of postcesarean delivery infectious complications compared with using povidone-iodine topical paint alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…An example is surgical site infections, which are affected by preoperative antibiotics and the abdominal preparatory process. 4 Process measures assess how the care system acts and do not assess the results of the care. Process measures are popular because they reflect actions of the care system and thus are able to be directly influenced by the health system.…”
Section: Current Measures Of Obstetrical Qualitymentioning
confidence: 99%
“…An example is surgical site infections, which are affected by preoperative antibiotics and the abdominal preparatory process. 4 Process measures assess how the care system acts and do not assess the results of the care. Process measures are popular because they reflect actions of the care system and thus are able to be directly influenced by the health system.…”
Section: Current Measures Of Obstetrical Qualitymentioning
confidence: 99%
“…These statistics have prompted investigation into the short- and long-term impact of cesarean delivery on fetal and maternal outcomes (35). Post-operative complication rates for both primary and repeat cesarean delivery vary widely and are reported anywhere from 5 to 35% (614). The most common causes of maternal peri-operative morbidity associated with cesarean delivery include surgical site infection and wound complications, hemorrhage, bowel/bladder injury and obstruction, and thromboembolic complications.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective cohort study comparing the traditional iodine paint technique to a protocol using a 3-minute iodine scrub in addition to the standard paint technique demonstrated that a scrub and paint preparation was associated with a decrease in the rate of postcesarean delivery infectious complications, such as endometritis, sepsis, cellulitis, peritonitis, and salpingitis, compared to the paint technique alone. 10 A major limitation of this study, however, is that not all patients received cefazolin prophylaxis preoperatively, a current standard practice described below. More patients in the ''Scrub and Paint'' group in the study, in fact, received antimicrobial prophylaxis.…”
mentioning
confidence: 99%